AN INTEGRATED REMOTE SENSING, GEOGRAPHIC INFORMATION SYSTEM AND ANALYTICAL HIERARCHY PROCESS FOR DETERMINATION OF GROUNDWATER POTENTIAL IN KEFFI-GRA AND ENVIRONS - Modibbo, Mahmud A.; Kana, A. A.; Bello, I. E.; Eya, A. I. (FUDMA JOURNAL OF SCIENCES, 2025)
Water, a universal solvent, is indispensable to all and has no adversary. The study area has experienced minimal depletion of some groundwater points, specifically boreholes. The groundwater potential of Keffi-GRA and its environs was assessed using remote sensing (RS), geographic information systems (GIS), and analytical hierarchy process (AHP) methods/techniques. These methods were adopted due to their ability to offer improved accuracy, visualization, reduced time and costs, and enhanced decision-making. The remotely sensed data used were Landsat 8 OLI (30 meters resolution) and SRTM DEM (30 meters resolution), while the GIS analysis was carried out on Arcgis Pro. The GIS analysis helped in delineating six thematic Map layers that influence the occurrence of groundwater (land use/land cover, slope, drainage density, water table, elevation, and rainfall); they were generated and weighted based on their importance using AHP. All the influencing factors were integrated and computed using the weighted overlay analysis tool on the software to generate the groundwater potential zones, five (5) zones where delineated, which reveals the area coverage of groundwater potential as 466m²/0.47km² (very low) covering 2.6% portion, 5,384m²/5.38km² (low) covering 29.23% portion, 3,416m²/3.42km² (moderate) covering 18.85% portion, 7,357m²/7.36km² (high) covering 40.68% portion, and 1,514m²/1.51km² (very high) covering 8.3% portion. To validate the results, a total of 90 groundwater points of boreholes and 20 hand-dug wells were used as validation points. Hence, the results from remote sensing, geographic information systems, and the analytical hierarchy process indicate the study area to have a moderate to high groundwater potential, with minor variations...